The Impact of Acute Stress Physiology on Skilled Motor Performance: Implications for Policing - Anderson, G. S.; Di Nota, P. M.; Metz, G. A. S.; Andersen, J. P. (Frontiers in Psychology, 2019)
Investigations of police performance during acutely stressful situations have primarily focused on higher-order cognitive processes like attention, affect or emotion and decision-making, and the behavioral outcomes of these processes, such as errors in lethal force. However, behavioral outcomes in policing must be understood as a combination of both higher-order processes and the physical execution of motor skills. What is missing from extant police literature is an understanding of how physiological responses to acute stress contribute to observed decrements in skilled motor performance at the neuromuscular level. The purpose of the current paper is to fill this knowledge gap in the following ways: 1. Review scientific evidence for the physiological (i.e., autonomic, endocrine, and musculoskeletal) responses to acutely stressful exposures and their influence on skilled motor performance in both human and animal models; 2. Review applied evidence on occupationally-relevant stress physiology and observed motor decrements in performance among police; and 3. Discuss the implications of stress physiology for police training and identify future directions for applied researchers. Evidence is compelling that skill decay is inevitable under high levels of acute stress, however, robust evidence-informed training practices can help mitigate this decay and contribute to officer safety.